An Analysis of the Implementation of Spiritual Well-Being Values in Early Childhood Based on Surah Luqman Verses 12–19: A Fisher's Theory Approach - Sukandar, Warlan (Indonesian Journal Publisher, 2025)
The aim of this study is to analyze the forms of instilling spiritual well-being values contained in Surah Luqman, verses 12–19, using John W. Fisher’s Spiritual Well-Being Theory. This theory highlights four main dimensions of spiritual well-being: the relationship with oneself (personal domain), with others (communal domain), with the environment (environmental domain), and with God (transcendental domain). This study focuses on how these four dimensions are reflected in the advice Luqman gave to his son, as recorded in the mentioned verses. The method used in this research is a qualitative approach with thematic content analysis techniques. The primary data source is the text of Surah Luqman verses 12–19, which is analyzed in depth and supported by relevant literature in Islamic exegesis and spiritual psychology. The results of the study reveal that these verses contain rich and applicable spiritual values for character development in children. The personal dimension is illustrated through the call to be grateful and to use wisdom; the communal dimension is reflected in the emphasis on doing good to parents and maintaining social relationships; the environmental dimension appears in the advice to walk humbly upon the earth; and the transcendental dimension is strongly conveyed in the call to worship Allah, establish prayer, and practice piety. These findings indicate that Surah Luqman is a strong source of spiritual education and can be integrated into early childhood education as a foundation for building holistic and sustainable spiritual well-being.